2018
DOI: 10.1002/acn3.557
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib treatment for severe refractory anti‐NMDA receptor encephalitis

Abstract: ObjectiveTo evaluate the therapeutic potential of bortezomib, a proteasome inhibitor that target plasma cells, in order to revive stalled recovery in patients with anti‐N‐methyl‐d‐aspartate (NMDA) receptor encephalitis who remain bedridden even after aggressive immunotherapy.MethodsWe consecutively enrolled patients with anti‐NMDA receptor encephalitis who remained bedridden after first‐line immunotherapy (steroids and intravenous immunoglobulin), second‐line immunotherapy (rituximab), and tocilizumab treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 29 publications
(43 reference statements)
0
26
0
1
Order By: Relevance
“…In contrast, in a five-patient case series with historical controls, Shin et al (16) report minimal improvements in clinical symptoms with no improvement in global modified Rankin Scale score following a bortezomib treatment of patients with severe anti-NMDA receptor encephalitis. Moreover, the study population demonstrated a comparable disease course to the historical control group.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In contrast, in a five-patient case series with historical controls, Shin et al (16) report minimal improvements in clinical symptoms with no improvement in global modified Rankin Scale score following a bortezomib treatment of patients with severe anti-NMDA receptor encephalitis. Moreover, the study population demonstrated a comparable disease course to the historical control group.…”
Section: Discussionmentioning
confidence: 87%
“…The treatment of refractory anti-NMDA receptor encephalitis represents a clinical challenge as it is often associated with longterm intensive care and significant morbidity (9,13,14,16). Here we describe a patient with a severe course of anti-NMDA receptor encephalitis without immediate response to first-and secondline treatment regimens of steroids, IVIG, plasma exchange, and rituximab.…”
Section: Discussionmentioning
confidence: 98%
“…A few studies in literature describe third-line treatments such as bortezomib (a proteasome inhibitor) or tocilizumab (an interleukin-6 receptor antagonist). [13][14][15][16] Our patient had short prodromal symptoms followed by en- brush. [17][18][19] The initial anti-NMDAR Encephalitis One-Year Functional Status (NEOS) score in our patient was 3 (required ICU admission, abnormal MRI, no clinical improvement after 4 weeks of treatment), which aided in the early initiation of second-line immunotherapy.…”
mentioning
confidence: 72%
“…Finally, for patients with severe and treatment-refractory disease, bortezomib [14] or tocilizumab [15] can be used as third-line therapy.…”
Section: Discussionmentioning
confidence: 99%